The Mascot : unraveling the mystery of my jewish father's nazi boyhood - Kurzem, Mark (Viking Books, 2007)
A survival story, a grim fairy-tale, and a psychological drama, this memoir asks provocative questions about identity, complicity, and forgiveness. When a Nazi death squad raided his Latvian village, Jewish five-year-old Alex escaped. After surviving the winter by foraging for food and stealing clothes off dead soldiers, he was discovered by a Latvian SS unit. Not knowing he was Jewish, they made him their mascot, dressing the little "corporal" in uniform and toting him from massacre to massacre. When the war ended he was sent to Australia with a family of Latvian refugees. Fearful of discovery--as either a Jew or a Nazi--Alex kept the secret of his childhood, even from his family. But he grew tormented and determined to uncover the story of his past. Shunned by a local Holocaust organization, he reached out to his son Mark for help in reclaiming his identity.--From publisher description